Exploring the function of myeloid cells in promoting metastasis in head and neck cancer - Dakota Dike Dimegwu Okwuone; Deri Morgan; Gregory N. Gan (Open Exploration Publishing Inc., 2024)
Head and neck cancer (HNC) is a challenging disease that lacks effective treatment, particularly in the cases that spread locoregionally and metastasize distantly, dramatically reducing patient survival rates. Expanding the understanding of the mechanisms of the metastatic cascade is critical for creating more effective therapeutics that improve outcomes for HNC patients. A true grasp of cancer metastasis requires the consideration of all cell types that contribute to the inflammatory HNC microenvironment as drivers of this process. More emphasis now is being placed on exploring the roles of the different immune cells in cancer control, tumorigenesis and metastasis. Myeloid cells are the most numerous immune cell types in the body, and they are actively recruited and reprogrammed by tumor cells to behave in a variety of ways. These cells are remarkably diverse in phenotype and function, and the part they play in tumor spread greatly differs based on the cell type. This review will focus on summarizing the roles of macrophages, neutrophils, myeloid derived suppressor cells (MDSCs), and dendritic cells (DCs) in driving HNC metastasis by examining the current knowledge base and offering potential new routes through which to target and treat this deadly process.